HUBUNGAN PARITAS, STATUS PEKERJAAN DAN MOTIVASI IBU DENGAN KEPATUHAN ANC PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PEKAUMAN BANJARMASIN - Tiaradevi, Tiaradevi; Latifah, Hj; Ariani, Malisa; Fetriyah, Umi Hanik (Jurnal Delima Harapan, 2024)
antenatal care visits carried out 4 times during pregnancy. The impact of non-compliance with ANC will result in maternal mortality (MMR). Factors causing non-compliance with ANC in pregnant women are parity, employment status and mother's motivation. Objective: To determine the relationship between parity, employment status and maternal motivation with ANC compliance among pregnant women in the Pekauman Banjarmasin Community Health Center working area. Methods: This type of quantitative research is an analytical survey with a cross sectional research design. This research was conducted in May-June 2024. The total sample was 30 respondents taken using a purposive sampling technique. Data were collected using questionnaires and observations of KIA books. Univariate and bivariate analysis used the Chi Square test. Results: There were 24 mothers who complied with the ANC examination (80.0%), parity 2-5 (multipara) as many as 18 people (60.0%), unemployed work status as many as 16 people (53.3%), respondents with 23 people (76.7%) had good motivation. The relationship between parity and ANC adherence (p=0.005<α0.05). relationship between employment status and ANC compliance (p=0.019<α0.05). Maternal motivation for ANC compliance (p=0.017<α0.05). Conclusion: There is no relationship between parity and ANC compliance, there is a relationship between employment status and maternal motivation and ANC compliance among pregnant women in the Pekauman Banjarmasin Community Health Center working area. It is recommended to carry out routine antenatal care (ANC) checks at least 4 times or more during pregnancy